Utilizing Realia to Enhance the Ability of the Ninth Grade Learners in Writing Procedure Texts - Sutanto Sutanto (Institut Agama Islam Negeri Palopo, 2021)
This research was aimed at enhancing the students’ ability of SMPN 1 Ungaran, Semarang in writing procedure texts through the utilization of realia as a media. This strategy is selected based on its strength in boosting learners to be more vigorously engaged in the teaching and learning process with the motive that their ability in writing procedure paragraphs grades. The research uses a collaborative classroom action research design where the researcher worked collaboratively. the process of the research activity in designing the lesson plan, determining the criteria of success, implementing the action, observing, and doing reflections. This research was done in 2 cycles, and each cycle involves three meetings. The data of this research are gained through an observation checklist, to get information about teacher’s and the students’ activities and performance during the application of the strategy, field notes, to record the data beyond the blanketing of the observation sheet, and writing test, to recognize the learners progress in writing procedure texts. The findings indicated that the refinement was shown by the upgrade of learners’ average writing scores from 53.36 in the preliminary test, 62.50 in the first cycle, to 70.14 in the second cycle. Also, the results of the research indicated that the learners were enthusiastic, motivated, and vigorously engaged in the teaching and learning process utilizing realia as media in the teaching and learning process.